Bile acids at neutral and acidic pH induce apoptosis and gene cleavages in nasopharyngeal epithelial cells : implications in chromosome rearrangement - Sang-Nee, Tan; Sai-Peng, Sim (BioMed Central, 2018)
Background: Chronic rhinosinusitis (CRS) increases the risk of developing nasopharyngeal carcinoma (NPC) while nasopharyngeal reflux is known to be one of the major aetiological factors of CRS. Bile acid (BA), the component of gastric duodenal contents, has been recognised as a carcinogen. BA-induced apoptosis was suggested to be involved in human malignancies. Cells have the potential and tendency to survive apoptosis. However, cells that evade apoptosis upon erroneous DNA repair may carry chromosome rearrangements. Apoptotic nuclease, caspase-activated deoxyribonuclease (CAD) has been implicated in mediating translocation in leukaemia. We hypothesised that BA-induced apoptosis may cause chromosome breaks mediated by CAD leading to chromosome rearrangement in NPC. This study targeted the AF9 gene located at 9p22 because 9p22 is one of the most common deletion sites in NPC.